What do we know about uncommon complications associated with third molar extractions? A scoping review of case reports and case series - Su, Naichuan; Harroui, Sana; Rozema, Fred; Listl, Stefan; Lange, Jan de; Heijden, Geert J M G van der (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2023)
The current study aimed to explore the types and frequencies of uncommon complications associated with third molar extractions based on a scoping review of case reports and case series. The study used an electronic literature search based on PubMed and Embase up to March 31, 2020, with an update performed on October 22, 2021. Any case reports and case series that reported complications associated with third molar extractions were included. The types of complications were grouped and the main symptoms of each type of complication were summarized. A total of 51 types of uncommon complications were identified in 248 patients from 186 studies. Most types of complications were post-operative. In the craniofacial and cervical regions, the most frequent complications included iatrogenic displacement of the molars or root fragments in the craniofacial area, late mandibular fracture, and subcutaneous emphysema. In other regions, the most frequent complications include pneumomediastinum, pneumorrhachis, pneumothorax, and pneumopericardium. Of the patients, 37 patients had life-threatening uncommon complications and 20 patients had long-term/irreversible uncommon complications associated with third molar extractions. In conclusion, a variety of uncommon complications associated with third molar extractions were identified. Most complications occurred in the craniofacial and cervical regions and were mild and transient.